AHL-priming functions via oxylipin and salicylic acid - Schenk, Sebastian T.; Schikora, Adam (Frontiers in Plant Science, 2015)
Collaborative action between the host plant and associated bacteria is crucial for the establishment of an efficient interaction. In bacteria, the synchronized behavior of a population is often achieved by a density-dependent communication called quorum sensing (QS). This behavior is based on signaling molecules, which influence bacterial gene expression. N-acyl-homoserine lactones (AHLs) are such molecules in many Gram-negative bacteria. Moreover, some AHLs are responsible for the beneficial effect of bacteria on plants, for example the long chain N-3-oxo-tetradecanoyl-L-homoserine lactone (oxo-C14-HSL) can prime Arabidopsis and barley plants for an enhanced defense. This AHL-induced resistance phenomenon, named AHL-priming, was observed in several independent laboratories during the last two decades. Very recently, the mechanism of priming with oxo-C14-HSL was shown to depend on an oxylipin and salicylic acid (SA). SA is a key element in plant defense, it accumulates during different plant resistance responses and is the base of systemic acquired resistance. In addition, SA itself can prime plants for an enhanced resistance against pathogen attack. On the other side, oxylipins, including jasmonic acid (JA) and related metabolites, are lipid-derived signaling compounds. Especially the oxidized fatty acid derivative cis-OPDA, which is the precursor of JA, is a newly described player in plant defense. Unlike the antagonistic effect of SA and JA in plant-microbe interactions, the recently described pathway functions through a synergistic effect of oxylipins and SA, and is independent of the JA signaling cascade. Interestingly, the oxo-C14-HSL-induced oxylipin/SA signaling pathway induces stomata defense responses and cell wall strengthening thus prevents pathogen invasion. In this review, we summarize the findings on AHL-priming and the related signaling cascade. In addition, we discuss the potential of AHL-induced resistance in new strategies of plant protection.